Novel reagent addition method for improved copper recovery - L. Forbes; C. Brill; I. Verster; G.V. Franks (Cleaner Engineering and Technology)
The development, implementation, and optimization of novel minerals processing technologies are of paramount importance in enabling a sustainable transition to renewable energy. One such technology is the processing of coarser mineral particles by fluidized bed flotation. While much attention has been given to the design of fluidized bed flotation equipment, equal attention is warranted towards the optimization of chemistry within these new devices. The detailed analysis of flotation thermodynamics has demonstrated that the addition of a collector on bubble surfaces carries advantages for improved collector absorption and enhanced mineral surface hydrophobicity.This paper continues our work in this field, where we conduct a detailed comparison of both traditional and aerosol collector addition methods in both conventional and fluidized bed flotation systems. The work demonstrates that the efficacy of aerosol collector addition significantly increases with increasing particle size. In the case of the coarsest size fraction tested (+425–850 μm), aerosol collector addition resulted in circa 50 % copper recovery, compared to circa 21 % using preconditioning under similar collector solution concentrations, with no detrimental effect of copper selectivity.